2021
DOI: 10.1038/s41417-021-00293-w
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA FLNA acts as a sponge of miR-486-3p in promoting lung cancer progression via regulating XRCC1 and CYP1A1

Abstract: Significantly high-expressed circFLNA has been found in various cancer cell lines, but not in lung cancer. Therefore, this study aimed to explore the role of circFLNA in the progression of lung cancer. The target gene of circFLNA was determined by bioinformatics and luciferase reporter assay. Viability, proliferation, migration, and invasion of the transfected cells were detected by CCK-8, colony formation, wound-healing, and transwell assays, respectively. A mouse subcutaneous xenotransplanted tumor model was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Although numerous studies have reported that miRNA expression is altered upon irradiation, studies exploring the mechanisms underlying these miRNA changes in response to irradiation are scarce. Recently, it has been reported that circular RNA can act as a sponge for miRNA to influence its function [ 37 , 38 , 39 ]. Thus, we attempted to look for links that might regulate miRNA production, starting from the miRNA production pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Although numerous studies have reported that miRNA expression is altered upon irradiation, studies exploring the mechanisms underlying these miRNA changes in response to irradiation are scarce. Recently, it has been reported that circular RNA can act as a sponge for miRNA to influence its function [ 37 , 38 , 39 ]. Thus, we attempted to look for links that might regulate miRNA production, starting from the miRNA production pathway.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Pan et al used a mouse lung cancer model to find that circFLNA promoted the proliferation, migration, and invasion of lung cancer cells through the sponge effect of miR‐486‐3p; the circFLNA‐miR‐486‐3p‐XRCC1/CYP1A1 regulatory axis was established through subsequent mechanistic experiments. 31 Gao et al screened the plasma of patients with persistent atrial fibrillation by circRNA microarray and found that hsa_circ_0004104 was significantly downregulated; hsa_circ_0004104 negatively correlated with TGF‐β1, suggesting the potential of hsa_circ_0004104 as a biomarker for persistent AF. 32 …”
Section: Discussionmentioning
confidence: 99%
“…the circFLNA-miR-486-3p-XRCC1/CYP1A1 regulatory axis was established through subsequent mechanistic experiments. 31 Gao et al…”
Section: Positioning and Sponge Function Of Hsa_ Circ_0000437mentioning
confidence: 99%
“…CircRNAs are considered promising biomarkers and therapeutic targets because of their sequence conservation, biostability, and tissue-specificity [ 17 , 18 ]. Among them, circFLNA is a newly discovered gene [ 19 ], and some studies revealed that overexpression of circFLNA, XRCC1, and CYP1A1 can promote survival and malignant development of cancer cells [ 20 ]. However, what effects circFLNA have on BCa remains to be determined, and given this uncertainty, this study regarding this field has carried out.…”
Section: Discussionmentioning
confidence: 99%